2018
DOI: 10.1021/acsbiomaterials.8b01239
|View full text |Cite
|
Sign up to set email alerts
|

Zwitterionic-Based Surface via the Coelectrodeposition of Colloid Particles and Tannic Acid with Bacterial Resistance but Cell Adhesion Properties

Abstract: Herein, a hydrophobized zwitterionic-based copolymer poly­(sulfobetaine methacrylate-co-2-(dimethylamino)­ethyl methacrylate-co-isobornyl acrylate) (P­(SBMA-co-DMA-co-ISA), PSDI) containing a chiral structure has been successfully synthesized by free radical polymerization and subsequent sulfonation reactions. Together with tannic acid (TA), PSDI colloidal particles (CPs) were anchored onto the Ti alloy surface by the electrophoretic deposition method. The composition, morphology, and surface properties of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Thus, it can be confirmed that SBMA is more easily hydrolyzed in a PBS environment due to the accelerated hydrolysis of esters in weakly alkaline PBS (pH = 7.4). The use of methacrylate-derived zwitterionic materials in the modification of metallic surfaces to enhance blood compatibility and endothelial cell proliferation is common . However, it is critical to assess if these materials will be stable or if they will undergo hydrolysis in the media they are incubated with.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it can be confirmed that SBMA is more easily hydrolyzed in a PBS environment due to the accelerated hydrolysis of esters in weakly alkaline PBS (pH = 7.4). The use of methacrylate-derived zwitterionic materials in the modification of metallic surfaces to enhance blood compatibility and endothelial cell proliferation is common . However, it is critical to assess if these materials will be stable or if they will undergo hydrolysis in the media they are incubated with.…”
Section: Resultsmentioning
confidence: 99%
“…The use of methacrylate-derived zwitterionic materials in the modification of metallic surfaces to enhance blood compatibility and endothelial cell proliferation is common. 46 However, it is critical to assess if these materials will be stable or if they will undergo hydrolysis in the media they are incubated with.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The borneol-based polymers are hydrophobic and noncytotoxic, which can significantly improve the cell adhesion ability [ 121 , 122 ]; on the other hand, borneol isomers on the material surface contribute to the surface bacterial resistance properties [ 119 , 120 ]. Due to those data, Meng et al [ 123 ] proposed polymerization with borneol based monomer, assuming that the hydrophobicity of zwitterionic polymers might increase, which will promote their cell adhesion ability without compromising their bacterial resistance properties. For this purpose, they synthesized hydrophobized zwitterionic copolymer P-(SBMA- co -DMA- co -ISA) (PSDI) (compound 149 , Figure 43 ), containing borneol based segment isobornyl acrylate (ISA) and zwitterionic moiety SBMA was prepared by sulfonation of P(DMA- co -ISA) (PDI).…”
Section: Monoterpene Bicyclic Derivativesmentioning
confidence: 99%
“… 126 TA and its derivatives are widely used as primers for immobilization of other molecules due to the presence of phenolic hydroxyl groups that could act as hydrogen bond donors. 127 The TA/SS coated surfaces were hydrophilic in nature. These surfaces were repellent to proteins and showed lower platelet adhesion and anti-adhesive bacterial properties ( Fig.…”
Section: Strategies For Improving Hemocompatibility Of Titanium-based Implantsmentioning
confidence: 99%